Development and application of wellbore flow assurance monitoring system for combustible ice production in deepwater - Kang, Qi; Peng, Qi; Chen, Hao-Qi; Wu, Hai-Hao; Song, Shang-Fei; Shi, Bo-Hui; Gong, Jing; Li, Ya; Huang, De-Xian (Geoenergy Science and Engineering, 2024)
The commercial development of combustible ice, as the most promising strategy energy, requires not only efficient gas production technology but also a safe flow assurance system. For the depressurization development of combustible ice in the sea area, the issues of wellbore fluid carrying sand, hydrate re-formation in the wellbore, and instability of wellbore flow, are the key problems leading to flow obstacles in the wellbore and affecting the normal production. Therefore, some measures must be taken to effectively monitor and analyze the flow situation in the wellbore during the development of combustible ice in the sea. In this paper, a Wellbore Flow Assurance Monitoring System (WFAMS) is developed to display the fluid flow conditions in the wellbore in real-time during the gas hydrate production, including temperature, pressure, flow rate, the carrying sand amount, etc. Furthermore, the system is capable of online monitoring for potential plug risks, including sand plugs and hydrate blockages caused by gas hydrate formation, as well as assessing flow stability. Additionally, it can provide valuable information, such as production adjustment data and the required injection dosage of thermodynamic inhibitors to prevent hydrate formation. In the 2020 South China Sea production test, this system was used for depressurization production and successfully predicted wellbore flow conditions. This enabled field engineers to monitor flow risks and adjust production plans in a timely manner, ensuring smooth test progress. •Development and application of Wellbore Flow Assurance Monitoring System.•Real-time monitoring and analysis of wellbore flow conditions.•Online analysis of the risk of sand plug and hydrate formation.